Pengaruh Kepercayaan Konsumen, Keamanan Dan Kepuasan Konsumen Terhadap Minat Beli Ulang Pada Toko Online Lazada - Rikasari Ambarita; Mauli Siagian (Economics and Digital Business Review, 2024)
This research was conducted with the aim of finding out the influence of Consumer Trust, Consumer Security and Consumer Satisfaction on Repurchase Intention at the Lazada Online Store. The population in this study are consumers who shop at the Lazada Online Store. Sampling used Jacob Cohen's theory and 204 respondents were selected. Quantitative research method with data collection techniques using questionnaires distributed to 204 respondents. Data analysis techniques using SPSS 27. The results of the research are (1) Consumer Trust in Repurchase Interest at the Lazada Online Store has a significant effect with t count 5,543>1,972 t table with level significance 0.000<0.05. (2) Consumer Security on Repurchase Interest at the Lazada Online Store has a significant effect on t count 8.310>1.972 t table with a significance level of 0.000<0.05. (3) Consumer Satisfaction with Repurchase Interest at the Lazada Online Store t calculated 2.659>1.972 t table with a significance level of 0.0<0.05. And (4) Consumer Trust, Consumer Safety and Consumer Satisfaction simultaneously/together influence Repurchase Intention at the Lazada Online Store, the F table value is 2.649, which means F count is 53.170 > F table 2.649 with a significance level of 0.000<0.05 .